PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR SENI BUDAYA KELAS III SEKOLAH DASAR NEGERI 5 KEMENUH GIANYAR - Ni Luh Putu Nginte Suryaningtyas; Ni Nyoman Mariani; Ni Kadek Supadmini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning motivation is one of the determining factors in achieving learning objectives, especially in Arts and Culture subjects at the elementary school level. Low student motivation may reduce participation, creativity, and learning outcomes. Therefore, an innovative learning model is required to encourage students to actively participate in the learning process. This study aims to analyze the implementation of the Project Based Learning model in improving the learning motivation of third-grade students in Arts and Culture at SD Negeri 5 Kemenuh Gianyar and to identify its impact on students during the learning process. This research employed a qualitative descriptive approach. The research subjects consisted of the principal, classroom teacher, and third-grade students. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Project Based Learning model was carried out systematically through project planning, project implementation, monitoring, product assessment, and evaluation. The application of this model increased students' enthusiasm, confidence, creativity, collaboration, responsibility, and active participation during learning activities. The study concludes that Project Based Learning is effective in improving students' learning motivation in Arts and Culture learning at the elementary school level.